Increased liver stiffness promotes hepatitis B progression by impairing innate immunity in CCl4-induced fibrotic HBV+ transgenic mice - Bybee, Grace; Moeun, Youra; Wang, Weimin; Kharbanda, Kusum K.; Poluektova, Larisa Y.; Kidambi, Srivatsan; Osna, Natalia A.; Ganesan, Murali (Frontiers in Immunology, 2023)
Background: Hepatitis B virus (HBV) infection is developed as acute or chronic liver disease, which progresses from steatosis, hepatitis and fibrosis to end-stage liver diseases such as cirrhosis and hepatocellular carcinoma (HCC). An increased stromal stiffness accompanies fibrosis in chronic liver diseases and is considered as a strong predictor for the disease progression. The goal of this study was to establish the mechanisms by which enhanced liver stiffness regulates HBV infectivity in the fibrotic liver tissue. Methods: For in vitro studies, HBV-transfected HepG2.2.15 cells were cultured on polydimethyl siloxane gels coated by polyelectrolyte multilayer films of 2 kPa (soft) or 24 kPa (stiff) rigidity mimicking the stiffness of the healthy or fibrotic liver. For in vivo studies, hepatic fibrosis was induced in C57Bl/6 parental and HBV+ transgenic (HBVTg) mice by injecting CCl4 twice a week for 6 weeks. Results: We found higher levels of HBV markers in stiff gel-attached hepatocytes accompanied by up-regulated OPN content in cell supernatants as well as suppression of anti-viral interferon-stimulated genes (ISGs). This indicates that pre-requisite “fibrotic” stiffness increases osteopontin (OPN) content and release and suppresses anti-viral innate immunity causing a subsequent rise in HBV markers expression in hepatocytes. In vitro results were corroborated by data from HBVTg mice administered CCl4 (HBVTg CCl4). These mice showed higher HBV RNA, DNA, HBV core antigen (HBcAg) and HBV surface antigen (HBsAg) levels after liver fibrosis induction as judged by a rise in Col1a1, SMA, MMPs, and TIMPs mRNAs and by increased liver stiffness. Importantly, CCl4-induced pro-fibrotic activation of liver cells and liver stiffness were higher in HBVTg mice compared with control mice. Elevation of HBV markers and OPN levels corresponded to decreased ISG activation in HBVTg CCl4 mice vs HBVTg control mice. Conclusion: Based on our data, we conclude that liver stiffness enhances OPN levels to limit anti-viral ISG activation in hepatocytes and promote an increase in HBV infectivity, thereby contributing to end-stage liver disease progression.